The Macroeconomic Impact of HIV/AIDS in Botswana - Sgherri, Silvia (IMF Working Papers; Working Paper ;, 2001)
This paper provides an overview of the potential macroeconomic effects of HIV/AIDS in Botswana, focusing on the key channels through which the pandemic is likely to affect the economic outlook and on the uncertainties involved. To estimate the impact of HIV/AIDS, a dual-economy equilibrium model is constructed and simulated under different scenarios. Depending on exactly how AIDS affects the outlook, GDP growth is projected to fall from around 5 1\2 percent a year without the pandemic to between 1 1\2 and 2 1\2 percent a year with AIDS. Non-negligible redistribution effects across sectors and labor skill categories are also likely to arise. Finally, the paper draws attention to the potential effects of HIV/AIDS on the long-term fiscal position of Botswana, highlighting the need for increased international support and/or lower drug prices so that the widespread introduction of anti-retroviral drug treatments is feasible.